Potential of phosphorylated nata de coco as cation-exchanger. - Menoza, Madel Q.
The potential of phosphorylated nata (p-nata de coco) as cation-exchanger was evaluated for univalent and dialent ions. The results obtained using the column technique showed that nata de coco has the potential to be a cation-exchanger for cadmium but not for potassium., Determination of the pH range at which the p-nata de coco is effective showed two inflection points and two pKa values which is near or within the pKA range of commercial p-cellulose . This confirms that the hydroxyl group in the cellulose matrix was converted to the phosphate group or there is phosphorylation reaction that occurred. The amount of titratable acid content of the sample falls within the range of the theoretical results. The p-nata de coco was also tested for its capacity to adsorb amino acids. The amount of serine adsorbed by p-nata de coco was determined qualitatively using ninhydrin test. Result of the test showed a light blue color compared to the very dark blue color of the control. This indicates that the p-nata de cocohas the potential to adsorb amino acids as well. Untreated nata de coco was also tested for its capacity to exchange with the amino acid serine. The tests showed a negative result for ninhydrin that implies that untreated nata de coco has no ion exchange capacity for amino acids.